1975
DOI: 10.1210/jcem-40-4-675
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Bioassayable and Immunoassayable Plasma ACTH and Cortisol Concentrations in Normal Subjects and in Patients with Cushing's Disease

Abstract: Plasma ACTH and cortisol concentrations were determined at 5-min intervals over a 3- or 4-h sampling period in 2 normal subjects. Time spans studied were 10:00 AM-1:00 PM, 4:00 PM-8:00 PM, 8:00 PM-11:00 PM, and 4:00 AM-8:00 AM. Similar sampling for 3 h, (onset 9:00-9:30 AM) was performed on 4 patients with Cushing's disease, 3 untreated and 1 in remission following pituitary irradiation. Two of these patients were studied on 2 separate occasions. Plasma ACTH was determined by both immunoassay (I) and bioassay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
33
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(40 citation statements)
references
References 0 publications
7
33
0
Order By: Relevance
“…The finding that one-third of all the cortisol pulses were not preceded by a significant rise in ACTH is consistent with previous studies in man and in the dog [3,19,30], and may be explained by postulating the existence of high-frequency ACTH pulses which remain undetected by a 10-min samp ling interval. Indeed, the pulse frequencies of all the measured substances were increased 3-to 7-fold when blood samples were withdrawn at 2-min intervals and, to our knowledge, these data provide the first in vivo evidence for the existence of high-frequency POMC-peptide and cor tisol pulses in any species.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The finding that one-third of all the cortisol pulses were not preceded by a significant rise in ACTH is consistent with previous studies in man and in the dog [3,19,30], and may be explained by postulating the existence of high-frequency ACTH pulses which remain undetected by a 10-min samp ling interval. Indeed, the pulse frequencies of all the measured substances were increased 3-to 7-fold when blood samples were withdrawn at 2-min intervals and, to our knowledge, these data provide the first in vivo evidence for the existence of high-frequency POMC-peptide and cor tisol pulses in any species.…”
Section: Discussionsupporting
confidence: 91%
“…However, when blood samples are taken at 10-min intervals, it may be ob served that the rise in plasma cortisol commences within 10 min of the secretion of ACTH [ 10,19).…”
mentioning
confidence: 99%
“…HA depletion also had a similar effect on the circadian ACTH rhythm: namely, the amplitude of the circadian rhythm of plasma ACTH decreased and it did not show a peak at the onset of darkness or a trough at the onset of the light period. The results were not so clear as those on the CS level, but fluctuation of the plasma ACTH level is reported to show a more irregular variation than that of plasma CS [14]; this may be partly because samples for ACTH must be obtained from different individual rats.…”
Section: Discussionmentioning
confidence: 75%
“…The 24-h cortisol profile demonstrated that the higher total cortisol levels in men with greater visceral obesity occurred during the hours from late morning to early evening, but not during the "trough" period between midnight and 0200 typically associated with Cushing's disease (20,28). Wallerius et al (47) described a similar pattern, using salivary FC measurements in men with higher vs. lower WHR during a limited daytime sampling period.…”
Section: Discussionmentioning
confidence: 86%